Efektivitas Pendampingan dan Penyuluhan Perpajakan dalam Mengatasi Surat Permintaan Penjelasan Atas Data dan/atau Keterangan (SP2DK) Pada Wajib Pajak di PT Pilar Teknologi Solusi, Cipondoh - Rachmawan, Mochamad Aditia; Purwanto, Dwi; Wungo, Yosef Tari; Saputri, Alzulin Olvica; Gunawan, Ester Hanna; Sugiyanto, Sugiyanto (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to evaluate the effectiveness of tax assistance and counseling in dealing with Letters of Request for Explanation of Data and/or Information (SP2DK) for taxpayers at PT Pilar Teknologi Solusi, Cipondoh. SP2DK is a letter issued by the Directorate General of Taxes (DJP) as a form of request for clarification of tax data and information that is deemed insufficient or not in accordance with applicable tax regulations. This research uses a descriptive approach with qualitative methods to analyze the influence of tax assistance and counseling on increasing taxpayer understanding and compliance in responding to SP2DK. The research results show that tax assistance and counseling provided by a team of tax experts can increase taxpayers' understanding of their tax obligations. Apart from that, this activity also helps taxpayers provide accurate and timely explanations regarding the data and information requested in the SP2DK. The majority of taxpayers at PT Pilar Teknologi Solusi showed a positive response to this mentoring and counseling program, which had an impact on reducing the number of SP2DK received and increasing the level of tax compliance at the company. From these results, it can be concluded that tax assistance and counseling has a very important role in reducing the risk of tax disputes and ensuring taxpayers fulfill their tax obligations correctly. Therefore, it is recommended that the tax assistance and counseling program be expanded and increase its effectiveness to achieve better tax compliance in the future.